The wolf keepers - Broach, Elise (Henry Holt and Company, 2016)
Twelve-year-old Lizzie Durango lives in a zoo, spending her days taking note of the animals' behaviors, then she meets runaway Tyler Briggs and together they investigate the wolves who are suddenly dying.